Jazz is “another possible way of perceiving the world...” [Review on the monograph: Matsenka, S. (ed.) (2019). Literaturno-dzhazovi improvizatsiï: intermedial′ni studiï (Literary-Jazz Improvisations: Intermedial Studies). Lviv : Sribne slovo, 396 p.] - Chervinska, Olha (Pitannâ lìteraturoznavstva, 2019)
Review on the monograph: Matsenka, S. (ed.) (2019). Literaturno-dzhazovi improvizatsiï: intermedial′ni studiï (Literary-Jazz Improvisations: Intermedial Studies). Lviv : Sribne slovo, 396 p.